2022
DOI: 10.3389/fnhum.2022.874703
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activity in Patients With Comitant Strabismus Detected by Analysis of the Fractional Amplitude of Low-Frequency Fluctuation: A Resting-State Functional MRI Study

Abstract: More and more studies showed that strabismus is not simply an ocular disease, but a neuro-ophthalmology disease. To analyze potential changes in brain activity and their relationship to behavioral performance in comitant strabismus patients and healthy controls. Our study recruited 28 patients with comitant strabismus and 28 people with matched weight, age range, and sex ratio as healthy controls. Using resting-state functional magnetic resonance imaging, we evaluated fALFF to compare spontaneous brain activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 26 Interestingly, a functional magnetic resonance imaging study found that, compared to controls, individuals with strabismus had significantly lower fractional amplitude of low-frequency fluctuation values in the left frontal superior medial gyrus and the right middle cingulum. 27 These studies suggest that strabismus and ADHD may share common structural anomalies in the central nervous system. Second, shared risk factors might account for the associations between ADHD and ophthalmological diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Interestingly, a functional magnetic resonance imaging study found that, compared to controls, individuals with strabismus had significantly lower fractional amplitude of low-frequency fluctuation values in the left frontal superior medial gyrus and the right middle cingulum. 27 These studies suggest that strabismus and ADHD may share common structural anomalies in the central nervous system. Second, shared risk factors might account for the associations between ADHD and ophthalmological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rs‐fMRI has been used widely in the field of neuroscience and neuropsychiatric diseases because it reflects the spontaneous neural activity of the human brain (Biswal et al., 1995 ). fALFF divides the energy of the calculated low‐frequency signal by the power of the whole frequency band, which effectively addresses the disadvantages of ALFF and improves the sensitivity and specificity of spontaneous neural activity signal detection (Hu et al., 2022 ). Moreover, the fALFF method has successfully been applied to several pain‐related diseases and is expected to have wide prospects (Table 3 ) (Dai et al., 2020 ; Li et al., 2021 ; Schneider et al., 2020 ; Wang et al., 2016 ; Zhang et al., 2019 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…fALFF divides the energy of the calculated low-frequency signal by the power of the whole frequency band, which effectively addresses the disadvantages of ALFF and improves the sensitivity and specificity of spontaneous neural activity signal detection (Hu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%